Enhancing the Economic Participation of Vulnerable Young Women in Solomon Islands - World Bank Group (World Bank, Washington, DC, 2019)
The aim of this study was to identify the constraints to, and effective measures for, increasing the economic participation of vulnerable young women in urban and peri-urban areas of Solomon Islands, in conjunction with the Community Access and Urban Services Enhancement (CAUSE) project. The study was funded by the East Asia and Pacific Umbrella Facility for Gender Equality of the World Bank. The findings serve three purposes: (i) inform ongoing policy discussions with the Honiara City Council (HCC) and the Ministry for Infrastructure Development (MID) on increasing young women's access to and participation in economic activities; (ii) inform the CAUSE project which is a World Bank financed project implemented by the HCC and MID, in coordination with the Guadalcanal, Malaita and Western Provincial Governments; and (iii) bring attention to and aid discussions with development partners supporting gender activities in Solomon Islands and the Pacific region, more generally. The report will also be publicly disseminated to foster a discussion about women's access to jobs. The study was framed within three key barriers to young women's economic participation: Knowledge and Skills, Resources, and Gender Roles. These were consistent with the three main gender outcomes highlighted in Towards Gender Equality and Prosperity: A Companion to the World Development Report (2012), i.e. endowments, economic opportunity, and agency. Decision-Making, although recognized as a participation barrier in the literature review, was not included, as influencing women's participation in policy, local governance, and planning processes would be beyond the scope of the CAUSE project and this study. Research areas which tackle barriers to both women's 'presence' (immediate engagement) and 'empowerment' (actions to effect social or behavioral change of women) in the economy were prioritized. The focus was also on research areas linked to interventions that could be enacted during the CAUSE project and lay the foundation for more sustainable and transformative change. Accordingly, the study was framed around three key questions: (i) What are the skills gaps among young women and how can these be addressed, including through training activities under the CAUSE project?; (ii) What challenges do young women face in accessing financial resources and what can be done to help build start-up capital?; and (iii) What gender related barriers do young women face in participating in training and work activities and what measures can be applied?